Addressing challenges in sealing of scalable multifiber module for O-2 enrichment using LSCF membranes - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (International Journal of Applied Ceramic Technology, 2022)
Scalable and multifiber modules in oxygen separation face huge challenges due to difficulty in integrating all the necessary components, especially in sealing the fibers in a gas tight module. Here, we report our findings on design and fabrication of a multifiber La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF)-based module, which can be scaled up. The focus is on sealing ceramic-metal interfaces by layering of sealants of varying thermal properties. We have also incorporated the use of dead ended fibers to minimize ceramic-metal interfaces in the hot zones and present a new method for dead ending by flame melting. Pressurizing the air inlet feed from either bore side or shell side is detrimental to the structural integrity of the fibers. A thorough characterization of the fresh and spent fibers is also carried out using X-ray tomography and electron microscopy, which indicates effect of temperature and pressure on the fibers.
Keywords: Characterization; permeability; Perovskites